Synthesis of 1, 2, 4- Triazole Derivatives And Their Biological Activity Study - Hussain, E. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study includes the synthesis of new derivatives of 1, 2, 4- Triazole which are contain Schiff bases derived from 1, 4, 5, 6- tetrahydropyrimidine. The structures of these derivatives were characterized from their melting points, infrared spectroscopy and elemental analysis. These derivatives were tested for inhibition of E-coli and were all found to be active